Strategy of Risk Adaptation for Local Maize Farmers Based on Livelihood Assets in Madura - Anisah Anisah; Abdul Wahib Muhaimin; Silvana Maulidah (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2021)
Local maize is the main food for Madura’s farmers. The initiation of superior hybrid seeds which causes the conversion of commodities from local corn to hybrid corn creates a lot of risks and losses. This study aims to 1) Analyze the level of access to livelihood assets of local corn farmers 2) Analyze the level of risk and level of adoption of local corn farmers’ adaptation strategies based on livelihood assets 3) The Effect of livelihood assets on strategy adoption. The research was conducted in Guluk-Guluk, Sumenep Regency. The analysis used is pentagonal assets analysis, descriptive analysis, and binary logistic regression. The results showed that the highest access of farmers to livelihood assets was access to social capital. The highest risk experienced by farmers is a technological risk. Meanwhile, the adaptation strategy chosen by the majority of farmers is hybrid crop diversification. Human capital, natural capital, and financial capital have a significant influence on the decision to adopt the adaptation strategy. So farmers need to adapt by maximizing their livelihood assets for better livelihood sustainability